Materials development and prospective for protonic ceramic fuel cells. (19th October 2021) - Bello, Idris Temitope; Zhai, Shuo; He, Qijiao; Cheng, Chun; Dai, Yawen; Chen, Bin; Zhang, Yuan; Ni, Meng
Summary: Protonic ceramic fuel cells (PCFCs) are considered a potential and more efficient upgrade to conventional solid oxide fuel cells (SOFCs). This is predominantly due to their capacity to operate efficiently at low and intermediate temperatures and their quality of nonfuel dilution at the anode during operation. This review presents a detailed exposition of the material development strategies for the major components of PCFCs (i.e., electrolyte, cathode, and anode) and how they differ from the traditional SOFCs. Credible science backed recommendations for the synthesis and fabrication of PCFCs materials are discussed. In the end, the opportunities, challenges, and future directions for P‐SOFCs are buttressed. Abstract : The review article presents a detailed exposition of the material developmental strategies for the electrolyte, cathode, and anode of PCFCs. The states‐of‐the‐art synthesis and fabrication techniques as well as prospective and scale‐up possibilities of PCFCs were thoughtfully and logically presented.